Peran Guru PAI Dalam Menanamkan Nilai-Nilai Toleransi Berbasis Islam di Madrasah Ibtidaiyah Daerah Minoritas - Pohan, Nurbiah; Robiah, Robiah; Habib, Muhammad (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2023)
This study aims to describe and analyze the role of Islamic Religious Education (PAI) teachers in instilling Islamic-based tolerance values ​​in Elementary Madrasahs located in areas with a non-Muslim majority, precisely in MIS Muhammadiyah Gunungsitoli, Nias. This study uses a qualitative approach with a phenomenological method. Data were collected through observation, in-depth interviews with teachers, madrasah principals, and students, as well as documentation studies. The results of the study indicate that PAI teachers design learning that systematically integrates tolerance values ​​through lesson plan planning, the use of exemplary stories of the Prophet Muhammad SAW, and student social activities. The implementation process takes place through a dialogical, contextual approach, and the habituation of tolerant attitudes in everyday life. The obstacles faced include the stereotypical views of society towards madrasahs, limited learning resources that discuss diversity, and the diverse family backgrounds of students. These findings indicate that PAI teachers have a strategic role as agents of religious moderation in the educational environment. The novelty of this study lies in the context of the location in a Muslim minority area and the phenomenological approach that explores the teacher's direct experience in instilling tolerance. This research contributes to the development of an inclusive Islamic education model that is responsive to the multicultural realities of Indonesian society.